2018
DOI: 10.1017/s1743921318006038
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dust precursors in envelopes of oxygen-rich AGB stars and red supergiants

Abstract: Condensation of circumstellar dust begins with formation of molecular clusters close to the stellar photosphere. These clusters are predicted to act as condensation cores at lower temperatures and allow efficient dust formation farther away from the star. Recent observations of metal oxides, such as AlO, AlOH, TiO, and TiO2, whose emission can be traced at high angular resolutions with ALMA, have allowed first observational studies of the condensation process in oxygen-rich stars. We are now in the era when de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In a future work, PAH-mineral interactions will be studied by utilizing more astrophysically relevant dust analogs, like olivines and pyroxenes, known to be present in meteorites alongside PAHs. , Hence, TiO 2 here serves as a tool to study the catalytic hydrogenation of PAHs. Nevertheless, TiO 2 has been suggested to be present in interstellar dust particles, , and it has been proven that one grain of TiO 2 could be enough to kick-start the nucleation of silicate dust particles …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a future work, PAH-mineral interactions will be studied by utilizing more astrophysically relevant dust analogs, like olivines and pyroxenes, known to be present in meteorites alongside PAHs. , Hence, TiO 2 here serves as a tool to study the catalytic hydrogenation of PAHs. Nevertheless, TiO 2 has been suggested to be present in interstellar dust particles, , and it has been proven that one grain of TiO 2 could be enough to kick-start the nucleation of silicate dust particles …”
Section: Introductionmentioning
confidence: 99%
“…54,55 Hence, TiO 2 here serves as a tool to study the catalytic hydrogenation of PAHs. Nevertheless, TiO 2 has been suggested to be present in interstellar dust particles, 56,57 and it has been proven that one grain of TiO 2 could be enough to kick-start the nucleation of silicate dust particles. 58 In this work, we analyze the interaction between the PAH molecules naphthalene, anthracene, and coronene and TiO 2 surfaces under vacuum conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consistently, astronomical observations have shown that the disappearance of AlO coincides with dust formation in a circumstellar outflow . It is assumed in astronomical studies that AlO either concentrated to form Al 2 O 3 solid or remained as Al-bearing gas phase species . Because sudden oxidation cannot occur in the dust-formation region, the incorporation of AlO molecules into the first minerals formed around evolved stars is possibly facilitated by the immiscible mechanism, inducing an anisotropy of Al 2 O 3 crystals.…”
Section: Discussionmentioning
confidence: 60%
“…[21] Additionally, Aluminium and carbon-containing smaller molecules have astrochemical significance due to their abundance in the interstellar medium. [22][23][24][25][26][27] A systematic comparative investigation of the structure, stability, reactivity, and bonding of charged and neutral clusters of AlnC1,2 0, is limited in the literature. Due to the vast applications of the atom-doped clusters in advanced materials, experimental and theoretical characterization of carbon-doped Al clusters (neutral and anionic) have gained a lot of attention over the last decade.…”
Section: Introductionmentioning
confidence: 99%